High-voltage flame-retardant electrolyte and application thereof
By adding fluorine-containing and cyano (sub)phosphate compounds to the lithium battery electrolyte, a stable SEI film and capture free radicals is solved, and the problem of poor electrolyte decomposition and compatibility of lithium batteries at high voltage is improved, and the circulation is improved Performance and safety, achieving high capacity retention and flame retardant performance.
Patent Information
- Application Number
- CN202411281223.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium batteries have problems such as electrolyte decomposition, insufficient stability of SEI membrane, damage to electrode structure and flammability under high voltage conditions, which limits their cycling performance and safety.
Fluorine-containing and cyano (sub)phosphate compounds are used as additives to form high-pressure flame retardant electrolyte. By constructing a stable LiF-Li3PO4 composite SEI film and complexing with the positive electrode material, free radicals are captured and the flame retardant of the electrolyte is improved. and compatibility.
Significantly improves the cycle life and safety of lithium batteries at high voltages, enhances the compatibility of electrolyte with positive and negative electrode materials, extends the service life of the battery, and maintains high capacity retention and flame retardant under high voltage conditions. performance.
Smart Images

Figure CN119275346A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-voltage flame-retardant electrolyte and application thereof. Background Art
[0002] With the rapid development of portable electronic devices and electric vehicles, lithium-ion batteries are increasingly used. However, the side reactions in the electrolyte are more serious at high voltages, which not only shortens the cycle life of the battery, but also may bring risks of internal short circuit and thermal runaway of the battery. Carbonate and ether solvents are prone to decomposition at high voltages, resulting in poor stability of the CEI and SEI membranes, increased internal resistance of the battery, weakened lithium conductivity, rapid decrease in cycle life, and poor battery safety due to the formation of lithium dendrites. These problems seriously restrict the performance of high-voltage lithium-ion batteries in terms of cycle performance, rate performance, and safety.
[0003] At present, the strategies for preparing high-voltage lithium battery electrolytes are: 1. Use highly fluorinated solvents or sulfone solvents; 2. Use additives such as vinyl sulfate and adiponitrile. However, highly fluorinated solvents have poor compatibility with lithium salts, sulfone solvents have high viscosity, vinyl sulfate additives can cause electrolyte discoloration and excessive acidity, and additives such as adiponitrile are difficult to form a stable CEI film. This has led to the difficult development of high-voltage lithium battery electrolytes.
[0004] Phosphate solvents or additives are usually used to flame retard electrolytes. Phosphorus-containing free radicals capture hydrogen radicals, the active ingredient in carbonate and ether solvents, thereby effectively reducing the flammability of the electrolyte. However, traditional (sub)phosphite additives have poor compatibility with the negative electrode. For example, they will destroy the layered structure of graphite, and the SEI film formed has poor stability, resulting in reduced battery performance. Summary of the invention
[0005] Technical issues solved:
[0006] This application addresses the deficiencies in the prior art and solves a series of challenges currently faced by lithium batteries under high voltage conditions, including technical problems such as electrolyte decomposition, insufficient stability of the battery SEI film, electrode structure damage, and easy combustion. It provides a high-voltage flame-retardant electrolyte and its application for removing fluoride in water, fully exerting the performance of high-voltage resistant positive electrode materials and extending their service life, reducing performance degradation during the cycle process, and improving the cycle life and safety of the battery under high voltage conditions.
[0007] Technical solution:
[0008] To achieve the above objectives, this application is implemented through the following technical solutions:
[0009] A high-voltage flame-retardant electrolyte, which is composed of a solvent, a lithium salt and a fluorine-containing, cyano (hypo)phosphite compound additive; wherein:
[0010] The fluorine-containing, cyano-containing (hypo)phosphite compound has a structure shown in formula (I) or formula (II):
[0011]
[0012] Wherein, R1, R2 and R3 are selected from one or two of fluorine atom, cyano chain alkoxy group and cyano cyclic alkoxy group alone or together; wherein the cyano chain alkoxy group is such as formula (III) and has 1 to 4 carbon atoms; the cyano cyclic alkoxy group is such as formula (IV) or formula (V);
[0013]
[0014] Furthermore, the mass fraction of the fluorine-containing and cyano (hypo)phosphite compounds is 0.1% to 12.0%.
[0015] Furthermore, the mass fraction of the fluorine-containing and cyano (hypo)phosphite compounds is 0.5% to 1.0%.
[0016] Furthermore, the solvent is one or more of carbonate, carboxylate and ether, and the solvent accounts for 10-45% of the total mass of the electrolyte.
[0017] Further, the carbonate is one or more of ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, ethylene carbonate EC, and propylene carbonate PC; the carboxylic acid ester is one or more of ethyl acetate EA, propyl acetate EP, ethyl propionate PA, and propyl propionate PP; the ether is one or more of ethylene glycol methyl difluoroethyl ether, ethylene glycol methyl trifluoroethyl ether, ethylene glycol methyl tetrafluoropropyl ether, ethylene glycol bisdifluoroethyl ether, ethylene glycol bistrifluoroethyl ether, ethylene glycol bistetrafluoropropyl ether, propylene glycol methyl difluoroethyl ether, (tris(2,2,2-trifluoroethyl)orthoformate, bis(2,2,2-trifluoroethyl) ether, and ethylene glycol dimethyl ether.
[0018] Furthermore, the lithium salt is one or more of lithium hexafluorophosphate LiPF6, lithium difluorophosphate LiDFP, lithium tetrafluoroborate LiBF4, lithium bis(oxalatoborate) LiBOB, lithium difluorooxalatoborate LiDFOB, lithium bis(difluorosulfonyl)imide LiFSI, and lithium bis(trifluoromethylsulfonyl)imide LiTFSI, and the lithium salt concentration in the electrolyte is 0.8 to 1.8 mol / L.
[0019] Furthermore, the lithium salt concentration in the electrolyte is 1.0-1.2 mol / L.
[0020] The present application also discloses the application of high-voltage flame-retardant electrolyte in lithium batteries. The negative electrode material used to assemble the lithium battery is graphite, silicon carbon or lithium metal; the positive electrode material used to assemble the lithium battery is lithium cobalt phosphate LiCoPO4, lithium cobalt oxide LiCoO2, lithium manganese oxide, lithium nickel manganese oxide or lithium nickel cobalt manganese oxide LiNi x Co y Mn 1-x-y O2(0.5≤x≤0.9, 0.1≤y≤0.5), NCM.
[0021] Furthermore, the negative electrode material used to assemble the lithium battery is lithium metal or silicon carbon Si@C, and the positive electrode material is NCM622 nickel cobalt manganese oxide LiNi 0.6 Co 0.2 Mn 0.2 O2 or lithium cobalt oxide LiCoO2.
[0022] Furthermore, the operation of assembling the lithium battery is carried out in a glove box with an ambient temperature of 18-25° C., an atmosphere of argon gas with a purity of 99.999%, and a moisture content of less than 0.01 ppm.
[0023] Beneficial effects:
[0024] The present application provides a high-voltage flame-retardant electrolyte and its application, which has the following beneficial effects compared with the prior art:
[0025] 1. The fluorine-containing and cyano (hypo)phosphite compounds of the present invention can not only construct a stable and ionically conductive LiF-Li3PO4 composite SEI film, but also can complex with transition metal ions of the positive electrode material to promote the formation of a stable oxidation-resistant CEI film, thereby inhibiting the contact decomposition of the electrolyte and the positive and negative electrode materials; in addition, the additive can capture hydrogen radicals and hydroxyl radicals in the electrolyte, making the electrolyte highly flame retardant and improving battery safety;
[0026] 2. The electrolyte preparation method provided by the present invention is simple, all steps are carried out under well-controlled environmental conditions, and it is easy to scale up production;
[0027] 3. The capacity retention rate of the NCM622||Li half-cell prepared by the electrolyte provided by the present invention after 100 cycles at a high voltage of 4.35V is 94.4%, while the capacity retention rate of the conventional basic electrolyte after 100 cycles is only 76.4%;
[0028] 4. Compared with the prior art in which the electrolyte has poor compatibility with the positive and negative electrode materials under high voltage conditions and may experience rapid capacity decay, the electrolyte of the present invention has a capacity retention rate of 87.6% and 86.4% respectively after 100 cycles at a high voltage of 4.35V in NCM622||Si@C and LiCoO2||Si@C full batteries, while the capacity retention rate of conventional basic electrolytes after 100 cycles is only 70.8% and 71.1% respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Comparison of the capacity retention rate data between Example 9 and Comparative Example 2 of the present application;
[0030] Figure 2 This is a charge-discharge curve diagram of the first cycle and 290 cycles of the cycle test at 1C in Example 9 of the present application, in which the electrolyte to which 1.0 wt% of compound ① is added is activated at 0.2C for two cycles in the voltage range of 3-4.35V in a NCM622||Si@C full battery system and then subjected to a cycle test at 1C. DETAILED DESCRIPTION
[0031] The above contents of the present invention are further described in detail below through examples, but the scope of the above subject matter of the present invention is not limited to the following examples. All technologies based on the above contents of the present invention that do not deviate from the structure of the present invention belong to the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.
[0032] A high-voltage flame-retardant electrolyte, which is composed of a solvent, a lithium salt and a fluorine-containing, cyano (hypo)phosphite compound additive; wherein:
[0033] The fluorine-containing, cyano-containing (hypo)phosphite compound has a structure shown in formula (I) or formula (II):
[0034]
[0035] Wherein, R1, R2 and R3 are selected from one or two of fluorine atom, cyano chain alkoxy group and cyano cyclic alkoxy group alone or together; wherein the cyano chain alkoxy group is such as formula (III) and has 1 to 4 carbon atoms; the cyano cyclic alkoxy group is such as formula (IV) or formula (V);
[0036]
[0037] The mass fraction of fluorine-containing and cyano (hypo)phosphite compounds is 0.1% to 12.0%; the solvent is one or more of carbonate, carboxylic acid ester and ether, and the solvent accounts for 10 to 45% of the total mass of the electrolyte; the carbonate is one or more of ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, ethylene carbonate EC and propylene carbonate PC; the carboxylic acid ester is one or more of ethyl acetate EA, propyl acetate EP, ethyl propionate PA and propyl propionate PP; the ether is ethylene glycol methyl difluoroethyl ether, ethylene glycol methyl trifluoroethyl ether, ethylene glycol methyl tetrafluoropropyl ether, ethylene glycol di The invention relates to a method for preparing an electrolyte comprising: preparing an electrolyte comprising: a first electrolyte and a second electrolyte; a first electrolyte and a second electrolyte; a second electrolyte and a second electrolyte; a first ...
[0038] Application of a high-voltage flame-retardant electrolyte in a lithium battery, wherein the negative electrode material of the lithium battery is lithium metal or silicon carbon Si@C, and the positive electrode material is NCM622 nickel cobalt manganese oxide LiNi 0.6 Co 0.2 Mn 0.2 O2 or lithium cobalt oxide LiCoO2, the operation of assembling lithium batteries is carried out in a glove box with an ambient temperature of 18-25°C, an atmosphere of argon with a purity of 99.999%, and the moisture in the atmosphere is less than 0.01ppm.
[0039] Embodiment 1:
[0040] A high-voltage flame-retardant electrolyte is prepared by sequentially adding lithium salt and fluorine-containing and cyano (hypo)phosphite compound additives into a solvent according to the formula in Table 1, maintaining the temperature constant at 25±5° C., and stirring evenly to obtain an electrolyte.
[0041] The structural formula of the fluorine-containing, cyano-containing (hypo)phosphite compound is one of the structures shown in formula (I-1) to formula (I-4):
[0042] Compound ① Compound ②
[0043] Compound ③ Compound ④
[0044] Application of a high-voltage flame-retardant electrolyte in a lithium battery, wherein the negative electrode material of the lithium battery is lithium metal or silicon carbon Si@C, and the positive electrode material is NCM622 nickel cobalt manganese oxide LiNi 0.6 Co 0.2 Mn 0.2 O2 or lithium cobalt oxide LiCoO2;
[0045] Half-cell assembly:
[0046] Preparation of positive electrode sheets: Mix the positive electrode material NCM622, conductive agent SuperP, and binder PVDF in a ratio of 94:3:3, disperse them in N-methylpyrrolidone, and stir until stable and uniform to form a positive electrode slurry. The material is scraped onto aluminum foil, dried at 80°C, rolled, cut into positive electrode sheets with a diameter of 12 mm, and further vacuum dried for use.
[0047] Preparation of negative electrode sheet: Cut the lithium metal positive electrode into 14mm diameter discs as the negative electrode sheet of the half-cell for future use.
[0048] Assemble the dried positive and negative electrode materials together with the diaphragm, use the diaphragm to completely isolate the positive electrode from the negative electrode, add 50μL of electrolyte to ensure that the electrode and lithium sheet are fully infiltrated, and use 800psi pressure for packaging to complete the assembly.
[0049] Embodiment 2-8:
[0050] A high-voltage flame-retardant electrolyte, the same as in Example 1, the high-voltage flame-retardant electrolyte is formulated according to Table 1, and the application of the high-voltage flame-retardant electrolyte in a lithium battery is the same as in Example 1.
[0051] Comparative Example 1:
[0052] An electrolyte, the same as in Example 1, the electrolyte is formulated according to Table 1, and the application of the electrolyte in a lithium battery is the same as in Example 1.
[0053] Examples 9-10
[0054] A high-voltage flame-retardant electrolyte, the same as in Example 1, the high-voltage flame-retardant electrolyte is formulated according to Table 1.
[0055] Application of high voltage flame retardant electrolyte in lithium battery, full battery assembly:
[0056] Preparation of positive electrode sheets: Mix the positive electrode material NCM622 or LiCoO2, the conductive agent SuperP, and the binder PVDF in a ratio of 94:3:3, disperse them in N-methylpyrrolidone, and stir until stable and uniform to form a positive electrode slurry. The material is scraped onto aluminum foil, dried at 80°C, rolled, cut into positive electrode sheets with a diameter of 12 mm, and further vacuum dried for use.
[0057] Preparation of negative electrode sheets: Mix the negative electrode material silicon carbon material, conductive agent SuperP, and binder SBR in a ratio of 94:3:3 and disperse them in deionized water. Stir until stable and uniform to form a negative electrode slurry. Apply it on the copper foil, dry it at 80°C, roll it, and cut it into negative electrode sheets with a diameter of 14 mm for later use.
[0058] Assemble the dried positive and negative electrode materials together with the diaphragm, use the diaphragm to completely isolate the positive electrode from the negative electrode, add 45μL of electrolyte to ensure that the electrode is fully wetted, and use 800psi pressure for packaging to complete the assembly.
[0059] Comparative Example 2-3:
[0060] An electrolyte, the same as in Example 1, the electrolyte is formulated according to Table 1, and the use of the electrolyte in a lithium battery is the same as in Examples 9-10.
[0061] Measuring the flammability of the electrolyte: Soak the fiberglass strips in the electrolyte and then conduct an ignition experiment to compare the flammability of different electrolytes.
[0062] Table 1 The electrolyte formulations of Examples 1 to 10 and Comparative Examples 1 to 3 of the present invention and the flammability of the electrolytes of Examples 5 to 8 and Comparative Example 1.
[0063]
[0064]
[0065] The charge and discharge cycle test was carried out in a 25°C constant temperature box using the Xinwei battery test system. The test results are shown in Table 2. The half-cell or full-cell prepared above was activated at 0.2C for two cycles, then charged to 4.35V at a constant current rate of 1C, then charged at a constant voltage to a current of ≤0.05C, and then discharged to 3V at a constant current for a charge and discharge cycle test. Capacity retention rate (%) = (current discharge capacity / initial discharge capacity) × 100%
[0066] Table 2 shows the positive and negative electrode materials of the batteries of the embodiments (1 to 10) and comparative examples (1 to 3) provided by the present invention and the capacity retention rate of the batteries during the cycle.
[0067]
[0068] Specifically, it can be seen from Tables 1 and 2 that the capacity retention rate of the NCM622||Li half-cell prepared by the electrolyte provided in Examples 1 to 8 after 100 cycles at a high voltage of 4.35V is 89.1-94.4%, and the electrolyte with an additive addition amount of 1wt% (Examples 5-8) has a better cycle performance than the electrolyte with an additive addition amount of 0.5wt% (Examples 1-4), and the capacity retention rate after 100 cycles can reach 92.8%-94.4%; while the basic electrolyte (hereinafter referred to as the basic electrolyte) in Comparative Example 1 to which no fluorine-containing and cyano (sub)phosphite compounds are added has a capacity retention rate of only 76.4% after 100 cycles at a high voltage of 4.35V, indicating that the addition of fluorine-containing and cyano (sub)phosphite compounds improves the compatibility of the electrolyte with the positive electrode.
[0069] Specifically, an electrolyte with excellent performance in the half-cell cycle performance (Example 1) is selected and applied to a full battery (Examples 9 and 10) composed of two positive electrode materials (NCM622 and LiCO2) and a silicon-carbon negative electrode (Si@C). The capacity retention rates after 100 cycles at a high voltage of 4.35V are 87.6% and 86.4%, respectively, and the capacity retention rates after 300 cycles are 71.5% and 68.5%, respectively. The discharge capacity of the NCM622||Si@C full battery (Example 9) is 181.8mAh / g in the first cycle, and 125.9mAh / g in the 290th cycle. The capacity retention rates of the NCM622||Si@C and LiCoO2||Si@C full batteries (Comparative Examples 2 and 3) composed of the basic electrolyte are 70.8% and 71.1% respectively after 100 cycles at the same voltage, and only 35.1% and 33.2% respectively after 200 cycles. The electrolyte with 1wt% compound ② added showed the best performance at high voltage in NCM622||Li half-cell, NCM622||Si@C full cell and LiCoO2||Si@C full cell, and the battery cycle stability was significantly improved. The electrolyte containing fluorine and cyano (sub)phosphite compounds of the present invention is not only compatible with high-voltage positive electrodes NCM622 and LiCoO2, but also beneficial to the performance of Si@C negative electrode. And compared with the traditional carbonate electrolyte, the electrolyte prepared by the present invention can be seen from the results of the combustion test (Examples 5 to 8 and Comparative Example 1) that the addition of fluorine and cyano (sub)phosphite compounds makes the electrolyte have high flame retardancy and improves battery safety.
[0070] As can be seen from the above, the technical solution of the present invention significantly improves the high-voltage resistance of the carbonate-based electrolyte by adding fluorine-containing and cyano (sub)phosphite compounds during the preparation of the electrolyte, thereby improving the cycle stability of the obtained battery under high voltage and reducing the performance attenuation of the high-voltage positive electrode material during the cycle. At the same time, the fluorine-containing and cyano (sub)phosphite compounds can construct a stable and ionically conductive LiF-Li3PO4 composite SEI film, and can complex with the transition metal ions of the positive electrode material, improve the compatibility with the high-voltage positive electrode, and promote the formation of a stable oxidation-resistant CEI film, thereby inhibiting the contact decomposition of the electrolyte and the positive and negative electrode materials. In addition, this additive can capture hydrogen radicals and hydroxyl radicals in the electrolyte, so that the electrolyte has high flame retardancy and improves battery safety. The electrolyte prepared by the technical solution of the present invention significantly improves the cycle performance and battery safety under high voltage conditions, and has good compatibility with a variety of positive and negative electrode materials.
[0071] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A high-voltage flame-retardant electrolyte, characterized in that: It is composed of a solvent, a lithium salt and a fluorine-containing, cyano (hypo)phosphite compound additive; wherein the fluorine-containing, cyano (hypo)phosphite compound has a structure shown in formula (I) or formula (II): Wherein, R1, R2 and R3 are selected from one or two of fluorine atom, cyano chain alkoxy group and cyano cyclic alkoxy group alone or together; wherein the cyano chain alkoxy group is such as formula (III) and has 1 to 4 carbon atoms; the cyano cyclic alkoxy group is such as formula (IV) or formula (V); 2. The high-voltage flame-retardant electrolyte according to claim 1, characterized in that: The mass fraction of the fluorine-containing and cyano (hypo)phosphite compounds is 0.1% to 12.0%.
3. The high-voltage flame-retardant electrolyte according to claim 2, characterized in that: The mass fraction of the fluorine-containing and cyano (hypo)phosphite compounds is 0.5% to 1.0%.
4. The high-voltage flame-retardant electrolyte according to claim 1, characterized in that: The solvent is one or more of carbonate, carboxylate and ether, and the solvent accounts for 10-45% of the total mass of the electrolyte.
5. The high-voltage flame-retardant electrolyte according to claim 4, characterized in that: The carbonate is one or more of ethyl methyl carbonate EMC, dimethyl carbonate DMC, diethyl carbonate DEC, ethylene carbonate EC, and propylene carbonate PC; the carboxylic acid ester is one or more of ethyl acetate EA, propyl acetate EP, ethyl propionate PA, and propyl propionate PP; the ether is one or more of ethylene glycol methyl difluoroethyl ether, ethylene glycol methyl trifluoroethyl ether, ethylene glycol methyl tetrafluoropropyl ether, ethylene glycol bisdifluoroethyl ether, ethylene glycol bistrifluoroethyl ether, ethylene glycol bistetrafluoropropyl ether, propylene glycol methyl difluoroethyl ether, (tris(2,2,2-trifluoroethyl)orthoformate, bis(2,2,2-trifluoroethyl) ether, and ethylene glycol dimethyl ether.
6. The high-voltage flame-retardant electrolyte according to claim 1, characterized in that: The lithium salt is one or more of lithium hexafluorophosphate LiPF6, lithium difluorophosphate LiDFP, lithium tetrafluoroborate LiBF4, lithium bis(oxalatoborate) LiBOB, lithium difluorooxalatoborate LiDFOB, lithium bis(difluorosulfonyl)imide LiFSI, and lithium bis(trifluoromethylsulfonyl)imide LiTFSI. The lithium salt concentration in the electrolyte is 0.8 to 1.8 mol / L.
7. The high-voltage flame-retardant electrolyte according to claim 6, characterized in that: The lithium salt concentration in the electrolyte is 1.0-1.2 mol / L.
8. Use of the high-voltage flame-retardant electrolyte according to any one of claims 1 to 7 in a lithium battery, characterized in that: The negative electrode materials used to assemble lithium batteries are graphite, silicon carbon or lithium metal; the positive electrode materials used to assemble lithium batteries are lithium cobalt phosphate LiCoPO4, lithium cobalt oxide LiCoO2, lithium manganese oxide, lithium nickel manganese oxide or lithium nickel cobalt manganese oxide LiNi x Co y Mn 1-x-y O2(0.5≤x≤0.9, 0.1≤y≤0.5), NCM.
9. The use according to claim 8, characterized in that: The negative electrode material used to assemble lithium batteries is lithium metal or silicon carbon Si@C, and the positive electrode material is NCM622 nickel cobalt manganese oxide LiNi 0.6 Co 0.2 Mn 0.2 O2 or lithium cobalt oxide LiCoO2.
10. The use according to claim 8, characterized in that: The lithium battery assembly operations are all carried out in a glove box with an ambient temperature of 18-25°C, an atmosphere of argon with a purity of 99.999%, and a moisture content of less than 0.01 ppm.
Citation Information
Patent Citations
Electrolyte additive, electrolyte, and secondary battery
CN113506916A
Non-aqueous lithium ion battery electrolyte and lithium ion battery
CN114865084A
Fluorophosphate, preparation method thereof, non-aqueous electrolyte containing fluorophosphate and electrochemical device
CN118271360A
Electrolyte additive composition, non-aqueous electrolyte containing additive composition and lithium ion battery
CN118380653A
Electrochemical device
US20230198096A1